Penggunaan Aromaterapi Lemon Untuk Mengurangi Nyeri Pada Pasien Post Operasi: Sebuah Studi Kasus - Zahri Darni; Ririen Tyas Nur Khaliza (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2020)
Post surgery is the third phase of surgery which begins with moving the patient from the operating room to the postoperative unit and ends with the patients discharge. Problems experienced after surgery patients include pain. Pain action can be overcome with pharmacological and non pharmacological actions. One of the non-pharmacological actions to deal with pain is the respiratory distraction technique, namely lemon aromatherapy. The purpose of this study was to obtain an overview of the implementation of lemon aromatherapy to reduce pain in postoperative patients. The method used is descriptive with a case study approach with data collection methods by interview, observation, physical examination and documentation study, The data collection instrument used a medical surgical nursing assessment format and lemon aromatherapy instrument. The data obtained were analyzed descriptively to describe changes in pain scale, facial expressions, pain intensity, blood pressure, and pulse frequency. The results showed a decrease in pain in both cases. Case I decreased pain scale from 6 to 3, pain intensity became mild, facial expression relaxed, blood pressure 122/80 mmHg, and pulse rate 86 x/minute. Case II, there was a decrease in the pain scale from 5 to 2, the pain intensity become mild, the facial expression looked relaxed, the blood pressure was 130/80 mmHg, and the pulse rate was 88x/minute. The conclusion of this study is that lemon aromatherapy can reduce pain in postoperative patients